Analysis and research on the influence of music on students’ mental health under the background of deep learning - Wang, Tianying; Zhao, Ying; Yin, Maoyuan (Frontiers in Psychology, 2022)
This paper makes a detailed analysis and Discussion on the impact of music appreciation on College Students' mental health. The influence of music appreciation on students' mental health, mental energy and mental structure. There has long been the idea of music promoting people's mental health, as well as related research in the field of music psychology. For this specific group of primary and secondary school students, it should be said that it is relatively rare to consider using music education to promote their mental health. This paper summarizes the advantages of deep learning over shallow learning, explains the necessity of introducing deep learning, and describes the data representation of deep learning and several typical deep learning models. This study adopts the method of multi evidence to conduct in-depth research and analysis. On the basis of in-depth study and research, this paper analyzes and studies the impact of music on students' mental health, so as to lay a foundation for future research on students' mental health. In terms of influencing factors and strategies to promote students' in-depth learning, we should apply the research results to specific teaching situations with the help of advanced digital technology, and strive to combine theory with practice. The research shows that college students' mental health is an important part of quality education in Colleges and universities, and music education plays an important role in the implementation of quality education.